Together But Alone: Human Isolation In The Digital Era - Erensoy, Şirin (Medimond S R L, Via Maserati 5, 40128 Bologna, 00000, Italy, 2012)
In recent years, there has been a massive homogenization of lifestyles and habits. This is due to the speed of globalization in the 21st century and the increased use of the World Wide Web as a result of it. The Internet has taken over every aspect of our lives - even things that we don't even question anymore. This sense of hyperreality that has taken over our lives is deceptive and clearly an illusion. The Internet and what it has to offer has slowly taken over human contact and communication. Now, we are more inclined to talk to a machine than to have face-to-face time. Though there might be a sense of comfort in communicated from behind a shield, it has led to human relations to strain and conversations to wither. This study will look at observations made on the 21st century youth and their Internet usages. The reasons why Internet usage has increased in recent years will be analyzed. Furthermore, the role of the Internet for social activism will also be evaluated.
Keywords: globalization; internet; online friendships; social activism; küreselleşme; çevrimiçi arkadaşlıklar; sosyal aktivizm